PENGARUH PENGGUNAAN MEDIA WHATSAPP (WA) GROUP TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI SISTEM GERAK PADA MANUSIA - Popo Musthofa Kamil (Institut Pendidikan Indonesia IPI Garut, 2019)
ABSTRACTThe research was conducted for the purpose of know the influence of the media whatsapp ( wa ) group of the results of students learning to the matter of moving systems on human beings in class VIII public junior high schools in 19 cities tasikmalaya. Study was conducted in august 2018 until october 2018 in smpn 19 tasikmalaya city. Methods used in research is true experimental design. The population of the research is all students viii smpn 19 tasikmalaya city about ten class, as the number of students about 248 orang. Sampel used by two class taken by cluster random sampling the class viii g as many as 30 students and class VIII G there 32 students. Research instruments is the test study results to the matter of moving systems in humans. This test of compound choice as many as 50 point about four option. Analysis techniques the data used was the standard significant t (α) = 5 %. Based on the research results show that is the media uses whatsapp ( wa ) group of the results of learning school tuition to the matter of moving systems on human beings in class viii junior high schools 19 tasikmalaya city years lessons 2018 / 2019. Keyword: Media wa group , mechanical systems in humans, study results